Review of A Conceptual Framework for Designing and Building Fisheries Co-management - Pahlevi, Reza Shah (Jakarta Technical University of Fisheries, 2024)
There has been growing consensus in fisheries management literature that fisheries can only be managed successfully with the power-sharing and partnership of fishers. The objective of this review is to focus on examining the current global literature on fisheries co-management. The review findings lead to the conclusion that various forms of fisheries co-management exist in many countries and have different organizational forms in different fishery settings. The review has identified six principles that should be applied in designing proper fisheries co-management: subsidiarity, conflict and power, property rights, representation and knowledge, community institution building and management functions.